Loving people even if they don’t love your comfort back - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
This article is a commentary and an additional study to translate into Russian the article of the American philosopher Sara Protasi published in this journal. In the article specific version of property view of love considered and compared with the existentialist view of this phenomenon